CULTURAL AND AESTHETIC SIGNIFICANCE OF JINGDEZHEN CERAMIC SCULPTURE IN HOTEL SPACE DESIGN - ZhuXu; Hapiz, Hana Yazmeen; Kamaruzaman, Azmul Fadhli (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This study explores the cultural and aesthetic significance of Jingdezhen ceramic sculpture in hotel space design. Jingdezhen, known as the "Millennium Porcelain Capital," has a rich history of ceramic artistry, which continues to influence contemporary design practices. This research examines how these sculptures transcend their historical and technical roots, becoming a vital cultural bridge in modern hospitality spaces. By integrating Jingdezhen ceramics into hotel interiors, this study enhances both spatial aesthetics and guest experiences. The research employs a mixed-methods approach, including case studies, interviews, and surveys, to assess how these sculptures contribute to cultural identity, emotional resonance, and aesthetic value in hotel environments. The findings highlight the sculptures' ability to create cultural depth and spatial harmony, offering actionable strategies for designers to incorporate this traditional art form into contemporary hotel design. This paper aims to further the understanding of how Jingdezhen ceramics can enrich modern design while preserving cultural heritage.